2012
DOI: 10.1371/journal.pone.0037346
|View full text |Cite|
|
Sign up to set email alerts
|

Evolution of Eye Morphology and Rhodopsin Expression in the Drosophila melanogaster Species Subgroup

Abstract: A striking diversity of compound eye size and shape has evolved among insects. The number of ommatidia and their size are major determinants of the visual sensitivity and acuity of the compound eye. Each ommatidium is composed of eight photoreceptor cells that facilitate the discrimination of different colours via the expression of various light sensitive Rhodopsin proteins. It follows that variation in eye size, shape, and opsin composition is likely to directly influence vision. We analyzed variation in thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
142
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(170 citation statements)
references
References 77 publications
22
142
0
Order By: Relevance
“…Further genetic and molecular analysis of the head shape differences will contribute to the growing number of studies examining the evolutionary genetics of shape and form. In particular, our analyses will complement similar approaches in understanding the patterning differences between closely (Arif et al, 2013; Posnien et al, 2012) and distantly (Carr et al, 2005) related flies with subtle and extreme, respectively, head shape differences.…”
Section: Resultsmentioning
confidence: 88%
“…Further genetic and molecular analysis of the head shape differences will contribute to the growing number of studies examining the evolutionary genetics of shape and form. In particular, our analyses will complement similar approaches in understanding the patterning differences between closely (Arif et al, 2013; Posnien et al, 2012) and distantly (Carr et al, 2005) related flies with subtle and extreme, respectively, head shape differences.…”
Section: Resultsmentioning
confidence: 88%
“…The ratio of ommatidial subtypes is stable amongst higher Diptera [33,108,109], yet subtle differences amongst drosophilids have been reported [110,111]. The data from more distantly related insects reviewed here show that some stochastic mosaics look surprisingly similar (honeybee workers, butterflies, and locusts), raising the possibility that patterning via factors similar to Spineless could be conserved.…”
Section: Discussionmentioning
confidence: 92%
“…Phylogenetic analysis shows that these Op10 rhodopsins are orthologs of the Drosophila Rh7 rhodopsin (Nene et al, 2007). This rhodopsin family is known to be present in the three mosquito species and the 12 Drosophila species for which there are characterized genomes (Posnien et al, 2012). The conservation of this rhodopsin family suggests that they may have a unique role in mosquito visual system function.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence comparison (Nene et al, 2007) showed that this Op10 rhodopsin belongs to a divergent group with greatest similarity to Drosophila Rh7, a rhodopsin of unknown function (Posnien et al, 2012). To initiate the study of this rhodopsin group, we characterized the expression profile of these mosquito genes.…”
Section: Introductionmentioning
confidence: 99%